OCURRENCE OF LINGULAPHOLIS (CRANIOPSIDAE, BRACHIOPODA) IN THE PIMENTEIRA FORMATION (DEVONIAN, PARNAÍBA BASIN) - Ribeiro, Victor Rodrigues [UNESP]; Sousa, Felipe Nascimento [UNESP]; Sedorko, Daniel; Matsumura, Willian Mikio Kurita; Ghilardi, Renato Pirani [UNESP] (UNESP - Universidade Estadual Paulista, 2023)
The genus Lingulapholis had temporal and spatial restrictions during the Devonian, being found only in Colombia and the United States. In Brazil, its related taxa Craniops is common in the Amazonas, Paraná, and Parnaíba basins. New data from the cities of Picos and Itainópolis, east flank of Parnaíba Basin, led to the discovery of a yet previously undescribed brachiopod genus for this region of Gondwana. The Lingulapholis brachiopod was found associated with plant fragments under conditions of moderate to low hydrodynamic energy as indicated by ichnological assemblage, in proximal expressions of Cruziana ichnofacies alternated to Skolithos ichnofacies. The presence of Lingulapholis suggests that the Parnaíba Basin was inserted in the zone of diffuse faunal mixing during the Middle Devonian.
REGISTRO DE LINGULAPHOLIS (CRANIOPSIDAE, BRACHIOPODA) NA FORMAÇÃO PIMENTEIRA (DEVONIANO, BACIA DE PARNAÍBA)
Keywords: Craniopsidae; Devonian; Gondwana; Ichnology; Lingulapholis